RUMAH REHABILITASI ODHA (ORANG DENGAN HIV/AIDS) - Jeffryco Pratama; Rudy Trisno (Jurusan Arsitektur dan Perencanaan, 2019)
HIV / AIDS is the most dangerous virus in the world that can be transmitted. People infected with this disease are called ODHA. At present they are not only fighting against the disease but they are also fighting against the bad stigma in society. With this negative stigma, ODHA are easily depressed and many ODHA choose to end their lives. For this reason, a rehabilitation center is needed to improve the standard of living for ODHA and the place of education for the HIV virus so that the stigma gradually diminishes. From studying the theory of the development of hospital typologies and the HIV / AIDS virus obtained a design method such as a). The hospital is open to the public, b). Sunlight affects the patient's mental and physical development, c). The circulation pattern of the hospital is in the form of aisle, d). Patients and the public can be combined if the disease is not contagious. In conclusion, the existence of a passage that can be traversed by the public and a program that triggers interaction between building users is expected to reduce the stigma of society and become a therapy for ODHA. So that ODHA have a strong mental life and will live their lives like Non-ODHA. Abstrak HIV/ AIDS adalah virus yang paling berbahaya didunia yang dapat menular. Orang yang terinfeksi dengan penyakit ini disebut ODHA. Saat ini mereka tidak hanya berperang melawan penyakitnya namun mereka juga berperang melawan stigma buruk pada masyarakat. Dengan adanya stigma negatif tersebut membuat ODHA mudah mengalami depresi dan bahkan banyak dari ODHA memilih untuk mengakhiri hidupnya. Untuk itu diperlukannya suatu wadah rehabilitasi agar meningkatkan taraf hidup ODHA dan wadah pendidikan virus HIV agar stigma tersebut lambat laun berkurang. Dari mempelajari teori perkembangan tipologi rumah sakit dan virus HIV/ AIDS didapatkan suatu metode perancangan seperti a). Rumah sakit terbuka untuk publik, b). Cahaya matahari memengaruhi perkembangan secara mental dan jasmani pasien, c). Pola sirkulasi rumah sakit berbentuk lorong, d). Pasien dan publik dapat digabung jika penyakit tidak menular. Kesimpulannya dengan adanya passage yang dapat dilalui publik dan program yang memicu interaksi antar pengguna bangunan diharapkan stigma buruk pada masyarakat berkurang dan menjadi terapi bagi ODHA. Sehingga para ODHA memiliki mental hidup yang kuat dan akan menjalani hidupnya layaknya Non-ODHA.